Differential Processing of Vertical Interfeature Relations Due to Real-Life Experience with Personally Familiar Faces. (April 2015) - Ramon, Meike
Identification of personally familiar faces is possibly the most complex and likewise efficient task achieved by the human visual system, yet to date the mechanisms underlying this extreme proficiency remain largely unknown. Building on empirical evidence from unfamiliar face processing in healthy populations and neuropsychological patients, the present work aimed to determine the type of information processed differently due to repeated, real-life experience with faces. A modulatory effect of familiarity was observed for processing of vertical interfeature distances, which have been suggested to rely on holistic processing skills. Contrariwise, no such effect was found for processing of information that can be discriminated locally (ie featural cues, interocular distances). The results indicate that familiarity-related advantages in face processing may arise from more efficient, or increased, holistic processing.